2021
DOI: 10.1007/s40747-021-00338-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel sEMG-based force estimation method using deep-learning algorithm

Abstract: This paper discusses the problem of force estimation represented by surface electromyography (sEMG) signals collected from an armband-like collection device. The scheme is proposed for the sake of two dimensions of sEMG signals: spatial and temporal information. From the point of space, first, appropriate channel number across all subjects is investigated. During this progress, an electrode channel selection method based on Spearman’s rank order correlation coefficient is utilized to detect signals from active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…In recent years, with the rapid development of computer technology, artificial intelligence has been applied in a wide range of fields, and many studies have applied neural networks to muscle force estimation based on the sEMG. Hua et al combined linear regression (LR) and LSTM to estimate muscle forces from sEMG signals [20], and the experiment results showed that the LR-LSTM performed well in muscle force estimation. Xu et al compared the performance of CNN, LSTM, and CNN-LSTM in estimating muscle forces from sEMG signals [21], and the experiment results showed that CNN-LSTM performed best.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of computer technology, artificial intelligence has been applied in a wide range of fields, and many studies have applied neural networks to muscle force estimation based on the sEMG. Hua et al combined linear regression (LR) and LSTM to estimate muscle forces from sEMG signals [20], and the experiment results showed that the LR-LSTM performed well in muscle force estimation. Xu et al compared the performance of CNN, LSTM, and CNN-LSTM in estimating muscle forces from sEMG signals [21], and the experiment results showed that CNN-LSTM performed best.…”
Section: Introductionmentioning
confidence: 99%
“…Although the training of deep neural networks may be lengthy, as the inference only involves a relatively simple forward pass through the network, it is computationally inexpensive and thus very quick. For instance, Hua et al [23] proposed a linear regression (LR) and long short-term memory (LSTM)integrated method (LR-LSTM) to predict the muscle force under the isometric contraction state. Tang et al [24] developed a modified framework to accurately predict muscle forces based on encoder-decoder networks.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, related traditional methods include linear discriminant analysis (LDA) [22], principal component analysis (PCA) [23], decision tree [24][25][26][27]. Deep learning algorithms have also been widely used in sEMG processing and behavioral intention recognition due to their ability to automatically learn data-representing features [28][29][30][31][32]. For instance, Wang et al proposed an sEMG Gesture recognition network by improving the multi-stream convolutional attention module, and achieved good results on the Ninapro DB1 dataset [31].…”
Section: Introductionmentioning
confidence: 99%